Ethnic Socialization and Perceived Discrimination on Ethnic Identity Among Transracial Adoptees: A Cross-Cultural Comparison Between Italy and the United States. (November 2017) - Ferrari, Laura; Hu, Alison W.; Rosnati, Rosa; Lee, Richard M.
There is limited research on how ethnic socialization and perceived discrimination concurrently contribute to ethnic identity development among transracial adoptees, and few studies have investigated these relationships across national contexts. Drawing upon the Phenomenological Variant of Ecological Systems Theory (PVEST) of human development, we examined the extent to which parental ethnic socialization and perceived discrimination as micro-level variables contribute to ethnic identity development among internationally adopted youth. Two different national contexts, the United States and Italy, as macro-level variables were examined as a potential moderator of these associations. Participants were 122 transracial adoptees living in the United States and 101 living in Italy (aged 15-20 years). In addition to adoptee survey reports, adoptive mothers completed a matching survey. Multisample structural equation modeling demonstrated parental ethnic socialization positively contributed to ethnic identity development in both groups. Cross-cultural differences emerged concerning the role of perceived discrimination. The ethnic identity of adoptees in Italy was negatively related to perceived discrimination, whereas there was no significant association among the adoptees in the United States. These findings highlighted the role of micro- and macro-levels of context in the ethnic identity development of internationally adopted youth.